THE INFLUENCE OF WORKPLACE WELL-BEING AND WORKLOAD ON THE PERFORMANCE OF EMPLOYEES WITH JOB STRESSAS AN INTERVENING VARIABLE IN EMPLOYEES OF THE REGENT'S OFFICE OF NUT ACEH DISTRICTA - Lizra Vanitra; Azhar; Nurmala; Ibrahim Qamarius (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to examine the effect of Workplace Well-Being and Workload on Employee Performance with Job Stress as an intervening variable in employees of the North Aceh district regent's office. The population in this study were civil servants (PNS) who worked at the North Aceh regent's office with a total of 127 people. Sampling in this study was carried out using probability sampling technique, namely proportionate stratified random sampling, with a sample size of 96 people. This study uses primary data sourced from questionnaires or questionnaires. The data analysis tool used is smartPLS 4.1.0.2. The results of this study indicate that workplace well-being has a significant impact on work stress, workload has a significant effect on work stress, workplace well-being has a significant impact on employee performance, workload is not significant to employee performance, work stress has no impact on employee performance, and work stress is not able to mediate the effect of workplace well-being and workload on employee performance.